Use of microencapsulated iron(II) fumarate sprinkles to prevent recurrence of anaemia in infants and young children at high risk - Zlotkin Stanley; Antwi Kojo Yeboah; Schauer Claudia; Yeung George (Bulletin of the World Health Organization, 2003)
OBJECTIVE: To compare the effectiveness of microencapsulated iron(II) fumarate sprinkles (with and without vitamin A), iron(II) sulfate drops, and placebo sprinkles in preventing recurrence of anaemia and to determine the long-term haematological outcomes in children at high risk of recurrence of anaemia 12 months after the end of supplementation. METHODS: A prospective, randomized, placebo-controlled design was used to study 437 Ghanaian children aged 8-20 months who were not anaemic (haemoglobin 5100 g/l). Four groups were given microencapsulated iron(II) fumarate sprinkles, microencapsulated iron(II) fumarate sprinkles with vitamin A, iron(II) sulfate drops or placebo sprinkles daily for six months. Primary outcome measures were change in haemoglobin and anaemic status at baseline and study end. Non-anaemic children at the end of the supplementation period were reassessed 12 months after supplementation ended. FINDINGS: Overall, 324 children completed the supplementation period. Among the four groups, no significant changes were seen in mean haemoglobin, ferritin or serum retinol values from baseline to the end of the supplementation period. During the trial, 82.4% (267/324) of children maintained their non-anaemic status. Sprinkles were well accepted without complications. At 12 months post-supplementation, 77.1% (162/ 210) of children with no intervention remained non-anaemic. This proportion was similar for children among the four groups. CONCLUSION: In most children previously treated for anaemia, further supplementation was not needed to maintain their non-anaemic status. These results may have important implications for community intervention programmes in which initial high-dose treatment is needed because of a high prevalence of anaemia.